Ionic liquids as phase transfer catalysts: enhancing the biphasic extractive epoxidation reaction for the selective synthesis of β-O-glycosides - Santiago, Cintia C. (2017)
Ionic liquids promoted the direct epoxidation of glycals acting as PTC. 1,2-anhydrosugars were prepared by the oxidation of glycals under biphasic conditions with dimethydioxirane generated in situ from oxone/acetone and amphiphilic IL’s as catalysts. β-O-glycosides were synthesized in good yields by the nucleophilic ring opening of epoxy carbohydrate derivatives. Also, 3,4,6-benzyl protected carbohydrates and β-N-glycosides could be prepare by this method.